Application and progress of transcranial substantial ultrasound in Parkinson's disease - Ma, Xishun; Li, Tongxia; Du, Lizhen; Han, Tongliang (Frontiers in Neurology, 2022)
Parkinson's disease (PD) is a common nervous system disease, mainly manifested as motor retardation, resting tremor, etc. (1). The clinical features of early PD patients are not characteristic, and diagnosis is very difficult. When obvious PD manifestations are found, the number of dopaminergic neurons in substantia nigra of patients has been reduced by more than half, and the treatment is difficult (2). Early diagnosis or auxiliary diagnosis of PD in clinical work is crucial for the treatment of PD and the prognosis of patients. In recent years, cerebral ultrasound has been widely used in the diagnosis and treatment of some diseases, such as Parkinson's disease, Alzheimer's disease, tuberculous meningitis, brain injury, etc., especially for the study of PD. The European Union of neuroscience and the latest diagnostic guidelines for PD in China have confirmed the role of the transcranial sonography (TCS). This article reviews the recent advances in the study of PD by transcranial sonography.